STR DIVERSITY OF A HISTORICAL SHEEP BREED BOTTLENECKED, THE CIKTA - E. Kovács; K. Tempfli; A. Shannon; P. Zenke; Á. Maróti-Agóts; L. Sáfár; Á. Bali Papp; A. Gáspárdy (Journal of Animal and Plant Sciences, 2019)
The population structure of the endangered Cikta sheep breed was evaluated by means of nine microsatellite polymorphisms. Seventy-two individuals from three flocks were sampled to determine genetic indices in the Hungarian population. Overall, average observed and effective allele numbers were 5.63 and 3.76, respectively. Discriminant analysis based on genotype frequencies revealed moderate genetic diversity among Cikta flocks, since only three loci (OarCP49, CSSM47 and OarHH41) contributed significantly (P<0.05) to differences between subpopulations. Low squared Mahalanobis distances from group centroids also confirmed that the breed is almost equally represented by the three flocks. Moderate level of diversity between flocks was attributed to the long-term effects of a population bottleneck dating back to the 1970s. Negative average FIS value (-0.18) indicated heterozygote excess. Chi-squared tests identified significant (P<0.05) deviation from HWE in the case of BM8125, CSSM47, and MAF214 markers. Continuous microsatellite information is required for the preservation of rare alleles and diversity in Cikta sheep.
Keywords: Cikta sheep; microsatellite; indigenous; population structure